KAJIAN KUALITAS AMBIEN UDARA DI KOTA SEMARANG (Studi Kasus: Jalan Setiabudi Dan Jalan Anton Sujarwo) - Warsiti Warsiti; Risman Risman; Ardhi Ristiawan (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2020)
It is hoped that the study of air quality monitoring in the area around the road can provide input to the Policy Provider regarding the number of motorized vehicles and road geometry planning so that air quality continues to meet health standards. The tool used in this study is a CO meter. Data was collected for 1 week on roads in Semarang by recording the number of vehicles passing within a certain period of time on roads with various road slopes and the amount of CO levels in the air. The data from the measurement results are compiled and then analyzed, namely analyzing the relationship between the amount of CO content in the air and the number of vehicles on the road with a certain slope. From the results of the analysis, the results will be obtained how much influence the number of passing vehicles with CO levels in the air on roads with certain slopes. The resulting output is a graph of the relationship between CO levels and the number of vehicles on various road slopes. The results showed that there was an increase in the amount of CO to the number of vehicles for the variation of the road slope of 0.5%, 2% and 5%. A significant increase in the amount of CO occurred during peak hours, namely 7.00 - 8.00 and 16.00 - 17.00 hours even exceeding the established threshold of 15,000 μg / Nm3.